2016
DOI: 10.3390/su8070684
|View full text |Cite
|
Sign up to set email alerts
|

Conjoint Analysis of Farmers’ Response to Conservation Incentives

Abstract: Environmental degradation threatens the long term resiliency of the US food and farming system. While USDA has provided conservation incentives for the adoption of best management practices (BMPs), only a small percentage of farms have participated in such conservation programs. This study uses conjoint analysis to examine Vermont farmers' underlying preferences and willingness-to-accept (WTA) incentives for three common BMPs. Based on the results of this survey, we hypothesize that federal cost share programs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 41 publications
(52 reference statements)
3
16
2
Order By: Relevance
“…They suggested that the incentives to be made to ensure maximum participation in adoption should be determined based on local costs. Conner et al [16] investigated the reasons for the lack of participation in the conservation incentive program to adopt the BMPs offered by United States Department of Agriculture (USDA) to prevent environmental degradation threatens the long term resiliency of the agriculture and food system in the USA based on the WTA. It was determined that the reason for the low participation was that the public incentives remained below the desired compensation and implementation costs by the farmers.…”
Section: Barriers To Sustainable Agriculture: Pricing and Public Supportmentioning
confidence: 99%
“…They suggested that the incentives to be made to ensure maximum participation in adoption should be determined based on local costs. Conner et al [16] investigated the reasons for the lack of participation in the conservation incentive program to adopt the BMPs offered by United States Department of Agriculture (USDA) to prevent environmental degradation threatens the long term resiliency of the agriculture and food system in the USA based on the WTA. It was determined that the reason for the low participation was that the public incentives remained below the desired compensation and implementation costs by the farmers.…”
Section: Barriers To Sustainable Agriculture: Pricing and Public Supportmentioning
confidence: 99%
“…In CA studies, a balance between statistical efficiency and response efficiency is sought 38. In this sense, an orthogonal array was used to reduce from 54 to 9 the number of cards presented in the survey, seeking to enhance the quality of the results 39. In addition, this unlabelled experiment offered different UHPs, each as a set of criteria (attributes) without identifying the points of mastitis control plan (eg, post‐dipping),28 which helped to reduce bias associated with particular interventions based on professional interests and/or personal gains 40…”
Section: Discussionmentioning
confidence: 99%
“…Conjoint analysis is a popular technique used in market research with the idea that a product can be described by its attributes and their levels. In recent years, it has been applied to a number of studies to estimate the farmers' preference towards varietal traits, seed sector, conservation incentives (Patil et al, 2006;Mafuru et al, 2007;Basavaraj et al, 2015;Conner et al, 2016,). The conjoint measurement allows estimation of the impact of individual attribute levels on the overall utility of a product (Annunziata & Vecchio, 2013) The first step of the analysis is to identify the appropriate attributes and their levels important to the farmers.…”
Section: Methodsmentioning
confidence: 99%